Superior mesenteric artery embolectomy and second-look laparoscopy technique in acute mesenteric ischemia: A case report (Annals of Medical Research, 2021)
None
Keywords: Acute mesenteric ischemia; ischemia-reperfusion injury; embolectomy; second-look laparoscopy